Effect of Pretreated Colza Straw on the Growth and Extracellular Ligninolytic Enzymes Production by Lentinula edodes and Ganoderma lucidum - Galina Makarenkova; Valda Balode; Dzintra Zala; Elina Azena; Alexander Rapoport; Indrikis Muiznieks (Fermentation, 2021)
Lentinula edodes 3565 and Ganoderma lucidum 9621 were compared for their ability to produce lignocellulolytic enzymes in submerged (SM) and surface liquid (SL) fermentation of hydrolysed colza straw lignin waste that remained after the production of furfural and bioethanol (CS lignin). Application of cultivated mushrooms to dispose of pretreated colza straw agricultural waste is an approach to decrease the quantity of residual lignin while simultaneously obtaining active substances, e.g., the ligninolytic enzyme complex from mycelium. The effect of adding CS lignin to culture media on the yield of L. edodes and G. lucidum mycelium and extracellular laccase activity was studied. It was revealed that the mycelial growth of G. lucidum on solid media was significantly improved by adding CS lignin. Laccase activity during SL cultivation of L. edodes on medium with CS lignin gradually increased over the experiment starting on day 21 and peaked at 520 U/mL on day 28. G. lucidum expressed the maximum laccase activity, 540 U/mL, during the first 14 days of mycelium SM cultivation. Extracellular laccase activity was enhanced about 35- to 40-fold at cultivation of L. edodes and about 10- to 15-fold in the case of G. lucidum by supplementing liquid culture media with CS lignin.